2015
DOI: 10.1159/000438793
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Progression of Diabetic Subclinical Macular Edema in Eyes with Mild Nonproliferative Diabetic Retinopathy: Location of the Increase in Retinal Thickness

Abstract: Purpose: To characterize the 1-year progression of retinal thickness (RT) increase occurring in eyes with subclinical macular edema in type 2 diabetes. Methods: Forty-eight type 2 diabetic eyes/patients with mild nonproliferative diabetic retinopathy (NPDR; levels 20 and 35 in the Early Treatment Diabetic Retinopathy Study) classified as presenting subclinical macular edema at baseline completed the 1-year follow-up period, from a sample of 194 followed in a 12-month observational and prospective study (Clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…Indeed, while previous experimental studies [32,33] reported an activation and hypertrophy (swelling) of Muller cells in the earlier stages of DR, other studies [18,34] showed an increased retinal thickness, which mainly occurs at the INL level, in the early stages of subclinical macular edema. This is likely related to the pathological alteration of the deep capillary plexus and extracellular accumulation of fluid.…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, while previous experimental studies [32,33] reported an activation and hypertrophy (swelling) of Muller cells in the earlier stages of DR, other studies [18,34] showed an increased retinal thickness, which mainly occurs at the INL level, in the early stages of subclinical macular edema. This is likely related to the pathological alteration of the deep capillary plexus and extracellular accumulation of fluid.…”
Section: Discussionmentioning
confidence: 93%
“…) or thickening of the INL in patients with subclinical macular oedema (Tejerina et al. ). In early diabetic macular oedema, the ONL is prone to the earliest thickening (Antcliff & Marshall ) and longitudinally the peripapillary RNFL has been reported to decrease with preceding intravitreal antivascular endothelial growth factor (Hwang et al.…”
Section: Discussionmentioning
confidence: 99%
“…The study was an investigator-driven observational study sponsored by the European Vision Institute Clinical Research Network (EVICR.net) [2]. Results of this study and procedures have been previously described [3,4,5]. …”
Section: Methodsmentioning
confidence: 99%